Eksplorasi Pariwisata Budaya: Tradisi Muharaman Desa Karangpakuan - Riki Taufik Nurcahaya; Gilang Pratama Putra; Tedi Supriadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tradition plays an important role in shaping cultural identity and social cohesion. Defined as the transmission of customs, beliefs, and practices from one generation to the next, tradition provides a sense of continuity and stability amidst the rapid changes of modern life. This encompasses various aspects of human experience, including rituals, celebrations, folklore, and social norms. Through tradition, communities preserve their historical narratives, moral values, and collective memories, creating a sense of belonging and shared purpose. The deepening of the Muharaman tradition in the Karangpakuan Tourism Village using the Exploration method is an effort to introduce and analyze the potential for developing the Muharaman tradition so that it can be recognized and preserved. Exploratory research methods are studies aimed at exploration, deepening knowledge, seeking new ideas, and formulating problems in more detail to then decide whether new research is necessary. The purpose of this research is to delve deeper into the Muharaman tradition and its potential as a tourist attraction using exploratory methods. This research uses a qualitative design with interviews as the main data collection method. The results of the data collection indicate that the Hajat Bakti Muharaman tradition is a tradition that emphasizes togetherness and social connections. The uniqueness of this tradition creates a great opportunity for it to be developed as a tourist attraction. However, the community's reluctance towards this tradition has somewhat hindered its development. Educational and promotional efforts are the initial steps that must be taken in developing this tradition as a tourist attraction.